¿Es adecuado el ABP en el aprendizaje de la fisiología? (2013)
The problem-based learning (PBL) as a teaching technique especially useful in medicine applied to clinical science of the profession, gives rise questioning the usefulness of this tool for meaningful learning of medical physiology, biomedical that as a core subject, is leading in the doctor's training, which is why there has been a search for articles and studies which showed the effectiveness of these forms of teaching and learning theories and support us in learning styles of students of medicine and science. This leads us to conclude the usefulness and importance of different techniques in the traditional teaching of physiology.